USULAN STRATEGI PERUSAHAAN DALAM RANGKA MENGHADAPI PERSAINGAN BISNIS DENGAN MENINGKATKAN PRODUK LOKAL PADA SEPATU MERK AA (Studi Kasus Pada Perusahaan Sepatu di PT Nikomas Gemilang) - AR. CHAERUDIN AR. CHAERUDIN (NIAGARA Scientific Journal, 2017)
Shoe industry in the field of competition is increasing these days, mentioned coupled with future conditions are more challenging and uncertain. External factors can be a threat and an opportunity for the company. Economic conditions due to the economic crisis in the region, including Indonesia, have bring down joints economy, including the industrial sector, so many national industry out of business. PT. Nikomas Gemilang as one of the companies engaged in the footwear industry requires a precise formulation of competitive strategy in order to survive and win the competition. Alternative formulation of this strategy consists of three stages: input stage (Input Stage), phase adjustment (Matching Stage) and the decision stage (Stage Decision). As a first step to identify external data and internal data company. At the input stage analyzed internal factors using the Internal Factor Evaluation (IFE) matrix while external factors using external Factor Evaluation (EFE) matrix. Phase adjustment is done using two matrices for generating strategic alternatives for the company, i.e., Strength-Weakness-Opportunities-Threats (SWOT) Matrix and Strategic Position and Action Evaluation (SPACE) Matrix. So that the resulting strategy is three alternative strategies to be used as material analyzed at a later stage. Decision stage analyzed using Quantitative Strategic Planning Matrix (QSPM). Of the three alternative strategies were chosen alternative strategy is the most suitable and the most likely to take into account the ability of the company, in thi case the "Strategy Market Development". Through the proposed business strategy is expected PT. Nikomas Gemilang able to increase market share and enhance the sustainable competitive advantage in the face of competition in the days to come.